Multisensory Input Modulates P200 and L2 Sentence Comprehension: A One-Week Consolidation Phase - Boustani, Nasim; Pishghadam, Reza; Shayesteh, Shaghayegh (Frontiers in Psychology, 2021)
Multisensory input is an aid to language comprehension; however, it remains to be seen to ‎what extent various combinations of senses may affect the P200 component and attention-‎related cognitive processing associated with L2 sentence comprehension along with the N400 ‎as a later component. To this aim, we provided some multisensory input (enriched with data ‎from three (i.e., exvolvement) and five senses (i.e., involvement)) for a list of unfamiliar words ‎to 18 subjects. Subsequently, the words were embedded in an acceptability judgment task with ‎‎360 pragmatically correct and incorrect sentences. The task, along with the ERP recording, was ‎conducted after a one-week consolidation period to track any possible behavioral and ‎electrophysiological distinctions in the retrieval of information with various sense combinations. ‎According to the behavioral results, we found that the combination of five senses leads to more ‎accurate and quicker responses. Based on the electrophysiological results, the combination of ‎five senses induced a larger P200 amplitude compared to the three-sense combination. The ‎implication is that as the sensory weight of the input increases, vocabulary retrieval is ‎facilitated and more attention is directed to the overall comprehension of L2 sentences which ‎leads to more accurate and quicker responses. This finding was not, however, reflected in the ‎neural activity of the N400 component.